PEMBELAJARAN MELAPORKAN PERISTIWA DENGAN PERLAKUAN MODEL EVALUASI DIRI DAN MODEL LATIHAN TERBIMBING BAGI PESERTA DIDIK KELAS VIII YANG TINGKAT KEMANDIRIANNYA BERBEDA - Molas Warsi Nugraheni (Universitas Tidar, 2016)
There are many obstacle faced in teaching learning of Bahasa Indonesia in Junior High School. Therefore, a repairement of teaching learning model which is acellerated with students’ condition and needs is needed. One alternative learning model that can be used is aplying Self Evaluation and Coaching Training model for students who have different level of independent. Self Evaluation model wich aplyed on students with have high level of independent has the average 88.33, on Students’ with low independent showed the average 67.92. Coaching Training model wich aplyed on students with have high level of independent has the average 69,17, on Students’ with low independent showed the average 75,50. The data proves that self-evaluation model is suitable implemented for students who have high level of independent, and coaching-training model is suitable for students with low level of independent.Keywords : Reporting a news, Model, Self-Evaluation, Coaching-Training, Independence.